Force of budget law preserving the integrity of the general appropriations act (2022)
Budget integrity requires that the budget disbursed by the government be the same budget authorized by Congress. However, realities on the ground demand flexibility in budget execution. This Note analyzes the extent of the President's power to adjust the general appropriations law. Using a rule-of-law framework, it is argued that the President's power of augmentation, as permitted by existing statutes, does not meet constitutional standards due to the absence of meaningful limitations in its exercise. This is aggravated by the perennial problem of underspending, which enables the transfer of billions of pesos from one item to another in the appropriations law. It is recommended that for the Executive to meet its mandate of the faithful execution of laws, tightened requirements for augmentation and other reforms be institutionalized in a separate budget systems law.
Keywords: Budget laws